Behavioural Problems and Parental Over-protectiveness in Children with Asthma - Sawant, Neena Sanjiv; Bhargava, Juhi; Deshmukh, Chandrahas T. (Journal of Nepal Paediatric Society, 2017)
Introduction: Asthma in children often leads to behavioural problems due to the chronic nature of the disease. Parents also tend to be overprotective and many may not even consult a doctor for the same. The objectives were to study the various behavioural problems seen in children having asthma as compared to those with minor ailments, parental awareness about the same and their parenting styles. Material and Methods: 75 parents of children of bronchial asthma and 75 parents of children having short term minor ailments formed the asthma and control groups respectively. The Behaviour Problem Index was used to assess the behavioural problems in children as documented by parents and parental overprotectivenesswas assessed using the Vulnerable Child/ Overprotecting Parent Scale. Results:The demographic variables were comparable in both the groups. Behavioural problems on all domains and parental over protectiveness in the asthma group were found to be statistically significant as compared to control group. However there was no significant correlation between the parental over-protectivenessand the behavioural problems in both the groups. Conclusions: Early referral to the psychiatrist with parental counselling will result in better outcomes for the child. J Nepal Paediatr Soc 2016;36(3):232-237